2022
DOI: 10.1097/j.pbj.0000000000000147
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and clinical characteristics of pediatric non-neoplastic posterior reversible encephalopathy: systematic review

Abstract: Background: Although more commonly seen in adult population, posterior reversible encephalopathy syndrome (PRES) can also be observed in pediatric patients. The etiopathogenesis of pediatric PRES is poorly understood, and the available evidence comes mostly from childhood cancer. Analysis of the sociodemographic and clinical characteristics of the different noncancer-related types can improve the understanding of pediatric PRES.Methods: Systematic review of characteristics and outcome of noncancer pediatric PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…79 PRES differs from the adult in aetiology, precipitants, and clinical manifestations. 2 The proportion of patients with combined anterior/posterior circulation was higher. 2…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…79 PRES differs from the adult in aetiology, precipitants, and clinical manifestations. 2 The proportion of patients with combined anterior/posterior circulation was higher. 2…”
Section: Discussionmentioning
confidence: 96%
“…[7][8][9] PRES differs from the adult in aetiology, precipitants, and clinical manifestations. 2 The proportion of patients with combined anterior/posterior circulation was higher. 2 In 2020, Wake et al 10 reported a case of PRES that developed during the treatment of severe burns in a 13-year-old boy.…”
Section: Aetiologymentioning
confidence: 96%
See 2 more Smart Citations
“…Pathophysiology of PRES-Hypertension Theory. PRES = posterior reversible encephalopathy syndrome chronic kidney disease, hypertension, and cardiomegaly(Jordao et al, 2022). Renal disease is the most common cause in children(Ando et al,…”
mentioning
confidence: 99%